THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 BENAI IN READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT - Sarizan '; Mahdum '; Eliwarti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research aimed to find out the ability of the second year students of SMAN 1 Benai in reading comprehension of analytical exposition text and to know the students’ lowest and highest score of reading comprehension components. The problems to be discussed are: how is the ability of the second year students of SMAN 1 Benai in reading comprehension of analytical exposition and which component is the students’ lowest and highest score in reading comprehension. The population of this research is all of the second year students of SMAN 1 Benai with the total is 170 students. The writer used Cluster Random Sampling technique to decide the research sample. This research used reading test as instrument which consisted of 40 multiple choice questions about 8 components of reading comprehension. After that, the instrument was tried out to make sure the validity and realibility of the test. From the data, it was found that the ability of the second year students of SMAN 1 Benai in reading comprehension of analytical exposition text is categorized into average level with the mean score 59,67. The findings also show that vocabulary component is the lowest score by the students with the mean score 51,86. On the other hand, social function component is the highest score by students the with the mean score 64,81. From the findings, further research can focus on the way to improve the students’ vocabulary in reading comprehension.Keywords: Ability, Reading Comprehension, Analytical Exposition text